Adsorption of Biologically Active Compounds from Aqueous Solutions on to Commercial Unmodified Activated Carbons. Part III. Theoretical Description of Paracetamol Adsorption Data at Neutral pH - Artur P. Terzyk (Adsorption Science & Technology)
A theoretical description of recently published paracetamol adsorption data on a series of non-modified commercial activated carbons is presented. Nineteen of the most widespread adsorption isotherm equations are analysed and the resulting maximum adsorption values compared. The equations proposed by Weber and Vliet, by O'Brien and Myers as well as by Dubinin and Astakhov led to the highest values of the average correlation coefficient describing the fit of the theoretical data to those obtained experimentally. On the basis of the results obtained as well as those published previously, the importance of carbon surface basic groups and carbonyl groups in the mechanism of paracetamol adsorption is emphasised.